Pengaruh Metode KodÃ¡ly Teknik Hand Signing Terhadap Kemampuan Memahami Notasi Solmisasi Lagu - Maulana, Aria Chandra; Gusrayani, Diah; Julia, Julia (Jurnal Pena Ilmiah, 2019)
Music art learning in understanding the solmisation notation in elementary schools still have many difficulties. Understanding the song solmisation notation is very important to learn especially in playing musical instruments. Difficulty understanding the notation can be solved using the Kodaly method of hand signing technique. The research method uses the experimental quasi method as well as the design of non-equivalent control group design research.Â  This research was conducted in one of the primary schools in Bandung, West Java, Indonesia with a total subject of 68 students in two classes studying in the fourth grade with a range of 9-10 years. The results showed that the increase in the experimental class averaged 39.70 to 51.67 and in the control class an average increase of the value of 38.23 to 45.58. This study showed an increase in the ability to understand song solmisation notation in experimental classes using the Kodaly method hand signing technique is better than the control class using conventional learning